A shortcut algorithm for solving long-term conjugate heat transfer problems based on quasi-steady flow. Issue 7 (2nd October 2017) - Dong, Sujun; Meng, Fanchao; Guo, Dechun; Kang, Hongling
Abstract : Purpose: The time of tightly coupled transient calculation and the accuracy of conventional loosely coupled algorithm make it difficult to meet the engineering design requirements for long-term conjugate heat transfer (CHT) problems. The purpose of this paper is to propose a new loosely coupled algorithm with sufficient accuracy and less calculation time on the basis of the quasi-steady flow field. Through this algorithm, it will be possible to reduce the update frequency of the flow field and devise a strategy by which to reasonably determine the update steps. Design/methodology/approach: In this paper, the new algorithm updates the flow field by solving the steady governing equations in the fluid region and by calculating the transient temperature distribution until the next update of the fluid flow, by means of solving the transient energy equations in the entire computational domain. The authors propose a strategy by which to determine the update step, by using the engineering empirical formula of the Nusselt number, on the basis of the changes of the inlet and outlet boundary conditions. Findings: Taking a duct heated by an inner forced air flow heating process as an example, the comparison results for the tightly coupled transient calculation by Fluent software shows that the new algorithm is able to significantly reduce the calculation time of the transient temperature distribution with reasonable accuracy. For example, the respective computing times are reduced to 22.8 and 40 per cent, while the duct wall temperature deviations are 7 and 5 per cent, using the two flow update time steps of 100 and 50 s on the variable inlet-flow rate conditions. Originality/value: The new algorithm outlined in this paper further improves the calculated performance and meets the engineering design requirements for long-term CHT problems.